THE EFFECT OF THE BENEFIT OF JOB ROTATION ON EMPLOYEE DEVELOPMENT - Tirajoh, Watson J.; Kindangen, Paulus .; Tielung, Maria V.J (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract : Generally a bank is a financial institution licensed by government of a country to provide loans, deposits, pay interest, financial transactions between one client to another and some financial services to its client. All of that can happen because employees of each of these banks that works in order to make it happen. The more qualified employee will give positive impact for each banks. Job rotation in this case, the employee will be in a division for a period of time and then moved to other division. Based on the background of job rotation in banks, researcher wants to do a research about the effect of the benefit of job rotation on employee development. The objective of this research is to analyze the effect of the benefit of job rotation on employee development. The type of this research is causal research, used Ordinal Regression Analysis and 100 sample. The result of this research shows that personal development and administrative knowledge have significant effect on employee development while employee interest, organization knowledge and technical knowledge have no significant effect to the dependent variable. Bank management should consider administrative knowledge and personal development because it affects employee development. This is important because job rotation will provide positive results for employee development when job rotation is well managed by management.Keywords : employee development, job rotation, ordinal regression